Substantial Carbohydrate Hydrolase Activities in the Water Column of the Guaymas Basin (Gulf of California) - Ziervogel, Kai; Arnosti, Carol (Frontiers in Marine Science, 2020)
The Guaymas Basin spreading center situated in the Gulf of California is characterized by a thick layer of organic-rich sediments that are thermally altered by hydrothermal fluids, thereby providing a bottom water source of dissolved organic carbon (DOC) to the water column. The potential for heterotrophic microbial communities in the water column to metabolize this organic matter source has not yet been investigated, however. In order to assess heterotrophic potential in the water column of the Guaymas Basin, we measured the activities of carbohydrate-hydrolyzing extracellular enzymes at the chlorophyll maximum, the oxygen minimum, the deep-water turbidity plume, and bottom waters. These measurements were carried out using water obtained from repeat CTD casts over the course of a week, and from bottom water collected by HOV Alvin at hydrothermally active areas with extensive chemosynthetic microbial mats. Repeat measurements at subsurface depths were very comparable across sampling dates and CTD casts. Exo-acting (terminal-unit-cleaving) monosaccharide hydrolase activities were typically higher in deeper waters than in surface waters, despite colder temperatures. In bottom water, the spectrum of endo-acting (mid-chain-cleaving) polysaccharide hydrolase activities was broader than at shallower depths. The high enzyme activities in Guaymas Basin bottom waters indicate an unusually active heterotrophic community that is responding to influx of DOC and nutrients into bottom waters from the hydrothermally affected sediments, or to the availability of chemosynthetically produced biomass.